The Case for BPA as an Obesogen: Contributors to the Controversy - Rubin, Beverly S.; Schaeberle, Cheryl M.; Soto, Ana M. (Frontiers in Endocrinology, 2019)
Since the inception of the term endocrine disruptor, the idea that the environment is an important determinant of the phenotype has motivated many of us to explore the effect of low dose exposure to BPA during organogenesis. The syndrome observed was complex, affecting various end points such as reproduction and reproductive tissues, behavior, mammary gland development and carcinogenesis, glucose homeostasis, and obesity. This constellation of end points suggests the possibility of complex interactions among the multiple effects of early BPA exposure. One main finding of our studies was that alterations of energy and amino-acid metabolism were detected soon after birth and continued to be present at all time points examined through 6 months of age. Classical manifestations of obesity and associated elements of metabolic disease took a longer time to manifest. Here we examine the validity of the often-mentioned lack of reproducibility of obesogenic effects of BPA, starting from the known environmental causes of variation, which are diverse and range from the theoretical like the individuation process and the non-monotonicity of the dose-response curve, to the very pragmatic ones like housing, feed, and time and route of exposure. We then explore the environmental conditions that may hinder reproducibility and examine the actual effect of confounding factors such as BPA-induced hyperactivity. In spite of all the potential sources of variation we find that the obesogenic effect of BPA is quite robust when the conditions of the studies compared are somewhat analogous, and we recommend that authors provide a description of the characteristics of the environment of these animals, from husbandry to feed. Finally, we show that when experimental conditions are strictly maintained for over a decade, a high reproducibility and stability of the obese phenotype is observed.